Language Assessment Literacy: Implications for Language Teachers (2018)
Recently, the applied linguistics field has examined the knowledge, skills, and principles needed for assessment, defined as language assessment literacy. Two major issues in language assessment literacy have been addressed but not fully resolved—what exactly language assessment literacy is and how it differs among stakeholders (e.g., students and teachers). This reflective article reviews assessment literacy from general education experts and language education scholars and shows how the meaning of language assessment literacy has expanded. To add to the discussion of this construct, the article focuses on the specific language assessment literacy for language teachers and proposes a core list of assessment knowledge, skills, and principles for these stakeholders.